2018
DOI: 10.1016/j.fertnstert.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in carriers of complex chromosomal rearrangements: a retrospective analysis of comprehensive chromosome screening results in seven cases

Abstract: The chances of identifying normal/balanced blastocysts in patients with CCR are <6%; the chances of a pregnancy are <4%. Greater complexity CCRs result in fewer transplantable embryos. Moreover, CCRs of greater complexity have a lower rate of high quality blastocysts than CCRs of less complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 26 publications
(33 reference statements)
0
27
4
Order By: Relevance
“…However, there was no significant difference in the fertilization rate, the embryo formation rate on Day3, and blastocyst formation rate among the three groups, suggesting that three types of BCCRs may have some differenteffects on high-quality blastocyst formation but not on embryos formation on Day3. A study showed that compared with exceptional CCRs, there was no significant difference in three-way rearrangements in the high-quality embryo rate on D3 after fertilization, while the former was significantly lower than the latter, which was inconsistent with our results [1] . Another study suggested some three-way complex translocations and complex CCR result in poor embryonic development, and were found to have more mosaicism.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, there was no significant difference in the fertilization rate, the embryo formation rate on Day3, and blastocyst formation rate among the three groups, suggesting that three types of BCCRs may have some differenteffects on high-quality blastocyst formation but not on embryos formation on Day3. A study showed that compared with exceptional CCRs, there was no significant difference in three-way rearrangements in the high-quality embryo rate on D3 after fertilization, while the former was significantly lower than the latter, which was inconsistent with our results [1] . Another study suggested some three-way complex translocations and complex CCR result in poor embryonic development, and were found to have more mosaicism.…”
Section: Discussioncontrasting
confidence: 99%
“…The application of PGT for BCCR carriers is controversial. Some scholars believedthat PGT is an effective fertility treatment for BCCR carriers, while others opposedit [1,18,19] . Twelve BCCR couples were treated with PGT, and two couples succeeded in getting pregnantand delivered healthy babies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations